Low velocity impact damage assessment of GLARE fiber-metal laminates interleaved by Nylon 6, 6 nanofiber mats. (1st May 2017) - Zarei, Hamed; Brugo, Tommaso; Belcari, Juri; Bisadi, Hosein; Minak, Giangiacomo; Zucchelli, Andrea
Abstract: GLARE is one of the most popular hybrid composite materials used in the aerospace structures which may be exposed to impact. Although the impact damage resistance of GLARE is better than its individual constituents i.e. aluminum and glass/epoxy composites, the poor strength of the lamina's interfaces causes failure modes such as delamination and debonding. Hence, the present research aims to increase the impact resistance of GLARE by nanofiber interleaving. Nylon 6, 6 nanofiber non-woven mats were fabricated by electrospinning technique and interleaved between the aluminum sheets and the glass fiber prepreg plies. Low velocity impact tests were performed on the nano-reinforced and the virgin laminates at 4 different impact energy levels: 6, 12, 18 and 32 J. The damage was evaluated by micrograph analysis of the impacted zone and visual inspection of the outer surface of the non-impacted side. Impact tests showed similar dynamic response for both laminate types. However, micrograph analysis revealed lower debonding length of the aluminum/glass fiber interfaces reinforced by Nylon 6, 6 nanofibers. Moreover, the analysis of the outer surface showed that Nylon 6, 6 nanofiber interleaving can reduce the damage area of GLARE by up to 62%.